The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/app.53698
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of biobased poly(ethylene 2,5‐furandicarboxylate) and polyglycolide acid blends under lipase conditions

Abstract: Bio-based polymer materials are considered to have function of protecting the environment, and improving the degradation performance of bio-based polymer materials is of great significance to realize the green cycle of production-use-degradation of plastic products. This present work is focused on the investigation of the degradation behavior of bio-based polymer blend poly(ethylene 2,5-furandicarboxylate) /polyglycolide acid (PEF/PGA) with different composition ratios in phosphate-buffered saline (PBS solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This indicates that the hydrophilicity and degradation rate of the structured mats were improved by increasing the PGA amount of electrospun nanofibers due to the fact that PGA has a much higher wettability than that of PCL, due to the multiple hydrophilic functional groups . In addition, it was also found in our previous study that, after PGA was introduced to the PEF matrix, the PEF/PGA blends exhibited obvious degradation behavior, and the mass loss rate of the blends increased with an increase of the PGA content because the high hydrophilicity of PGA accelerated the contact of PEF with enzymes and water . Despite this, the high crystallinity and high tensile strength of PGA cannot improve the flexibility of PEF.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…This indicates that the hydrophilicity and degradation rate of the structured mats were improved by increasing the PGA amount of electrospun nanofibers due to the fact that PGA has a much higher wettability than that of PCL, due to the multiple hydrophilic functional groups . In addition, it was also found in our previous study that, after PGA was introduced to the PEF matrix, the PEF/PGA blends exhibited obvious degradation behavior, and the mass loss rate of the blends increased with an increase of the PGA content because the high hydrophilicity of PGA accelerated the contact of PEF with enzymes and water . Despite this, the high crystallinity and high tensile strength of PGA cannot improve the flexibility of PEF.…”
Section: Introductionsupporting
confidence: 55%
“…In our previous study, we found that when PGA was introduced into the PEF matrix, significant mass loss of the PEF matrix occurred during the degradation process of the PEF/PGA blends within 8 weeks, indicating that the introduction of PGA components can indeed accelerate the degradation process of PEF. 24 Similarly, Guebitz et al found that the PEF homopolymer undergoes significant degradation behavior in the presence of cutinase. 51,52 Based on this, the degradation process of the PEF/PGACL blend was summarized in Figure 12G.…”
Section: Tensile Properties Of the Pef/pgacl Blendsmentioning
confidence: 93%
See 1 more Smart Citation
“…120 In addition, the hydrolysis of bio-based polymer blends, such as poly(ethylene 2,5-furandicarboxylate)/polyglycolide acid, can be achieved using porcine pancreas lipase in aqueous saline media. 121 Polyurethane (PU) is another plastic product with huge environmental impact. PU is produced per year on a global scale at 23.89 million metric tons in 2022 and with an increasing rate of 5% per year.…”
Section: (Bio)catalytic Depolymerisation Of Plastic Materialsmentioning
confidence: 99%
“…120 In addition, the hydrolysis of bio-based polymer blends, such as poly(ethylene 2,5-furandicarboxylate)/polyglycolide acid, can be achieved using porcine pancreas lipase in aqueous saline media. 121…”
Section: (Bio)catalytic Depolymerisation Of Plastic Materialsmentioning
confidence: 99%